Análisis de la aplicación de los códigos deontológicos de TC televisión y teleamazonas en la producción de sus noticieros estelares - Armijos Delgado, Sandra Janeth (2017)
To make this project, one of the main objectives was to analyze the application of deontological codes to journalistic practice in the media, specifically in two media that are the subject of this study, taking as a reference point TC Television for being a means of official editorial line and Teleamazonas with a marked political tendency of opposition, both demonstrate a great hearing and in the conformation of notes they hint their political differences. Based on this study, it was investigated and verified whether at present it is being fulfilled in these means of communication with the parameters established in the Organic Law of Communication that in its Article 10 establishes the application of these rules that regulate the journalistic exercise….